Pattern of Secondary Bacterial Infections and Antibiotic Susceptibility among Confirmed COVID-19 Patients at a Tertiary Care Hospital - Sabir, Nargis (International Journal of Pathology, 2022)
Introduction: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was identified as the cause of pneumonia cases in Wuhan, China, at the end of 20191. Secondary bacterial infection (SBI) is one of the lethal complications in hospitalized patients with COVID-19. Objective: To determine the pattern of SBIs and antimicrobial susceptibility among confirmed COVID-19 patients. Methodology: This cross sectional study was conducted at department of Pathology Combined Military Hospital Lahore from March-September 2020. Confirmed COVID-19 patients (n=1584) developing bacterial culture confirmed secondary bacterial infections (SBIs) were included. Antimicrobial susceptibility testing was performed by Modified Kirby Bauer disc diffusion method. Drug zones and mechanism of resistance among isolated bacteria was detected using CLSI guidelines. Results: SBIs were detected in 73 (4.6%) patients. Among 73 patients 47 (64%) developed ventilator associated pneumonia (VAP), 11(15%) had catheter related blood stream infections (CRBSI), 8 (11%) developed catheter associated urinary tract infection (CAUTI) and 7 (9%) had surgical site infections (SSIs).All bacterial isolates were multidrug resistant and 48(66%) were extensively drug resistant. Among isolated bacteria, Acinetobacter baumannii exhibited the highest resistance. The isolation rates of extended-spectrum beta-lactamases (ESBLs) producing Gram-negative rods, carbapenem-resistant A. baumannii (CRAB) and carbapenem-resistant Klebsiella pneumoniae were 100%, 91% and 61%, respectively. About 100% of isolated Staphylococci were methicillin-resistant Staphylococcus aureus (MRSA), and 33% of isolated Enterococci were vancomycin-resistant (VRE). Conclusion: Incidence of secondary bacterial infections in COVID-19 patients was 4.6%. VAP was the most common SBI followed by CRBSI, CAUTI and SSI respectively. High antimicrobial resistance was observed among isolated bacteria.